Monitorizarea mass-mediei privind patrimoniul mondial din România. Considerații preliminare - Cozma, Elena (Plural: History, Culture, Society, 2018)
Both, the general public and the specialists (archaeologists, historians, etc.) that are concerned with the cultural heritage, are most often informed about their state or about the latest archaeological discoveries in the written or TV press. The present study focuses on articles published in the press and television during 2017 and 2018 (January–November) on the issue of the cultural and archaeological heritage of Romania included into the UNESCO World Heritage List. For a better follow-up to this study, we will provide you with a table below with each UNESCO heritage objective, along with the LMI code, UNESCO registration code, year of listing and geographic location. Also, the study will contain a brief presentation of the report drawn from the media for each monument. The research is part of the project “Protecting by Development of Sustainable Strategies for a Better Protection of the UNESCO World Heritage Sites from Romania”, supported by CNCS-UEFISCDI, PN-III-P4-ID-PCE-2016-0737